A Study on Stakeholder Perspective Regarding the CSR Model for Indian Organizations: Some Key Issues - Pachar, Sunita; Singh, Rajbir (Prabandhan: Indian Journal of Management, 2013)
Purpose: There has been an increasing interest in corporate social responsibility (CSR) worldwide. For implementation of CSR in Indian organizations, this study was conducted to ascertain how Indian stakeholders perceive CSR, what they expect from Indian organizations, and which issues should Indian organizations give priority to while undertaking CSR initiatives. The research work also investigates the relationship between personal attributes (gender, marital status, age, and profession) and CSR practices dimensions. The paper analyzes whether there is any significant difference between the demographic variables and the concept of CSR practices in Indian organizations. Design/Methodology/Approach: The study is exploratory in character and falls under the category of "general review" aimed at gaining familiarity and achieving insights into the phenomena, that is, stakeholders’ perspective regarding the corporate social responsibility model in Indian organizations. Findings: The study found that the Environment dimension emerged as the most important factor which means that a company’s products should be eco-friendly and the organization should lay emphasis on reducing pollution and undertaking waste management initiatives. The Economic dimension emerged as the least important factor, which suggests that the organizations should not think that CSR is a costly concept or that CSR policies would have a negative impact on the company’s economic performance. Furthermore, the paper concludes with recommendations for organizations to develop and implement CSR programs for the betterment of the society.